Money supply, budget deficit and inflation dynamics in Ghana: An empirical investigation - Emmanuel Duodu; Samuel Tawiah Baidoo; Hadrat Yusif; Prince Boakye Frimpong (Cogent Business & Management, 2022)
The paper investigates the long run dynamics of money supply, budget deficit and inflation in Ghana. It also tests the validity of the classical, monetary and fiscal theories of price level within the vector error correction framework. Using quarterly data from 1999Q1 to 2019Q4, the paper employs Granger causality test and the vector error correction model (VECM) for the analysis. The results from the VECM show that budget deficit has a significant positive effect on inflation while money supply negatively affect it. By contrast, inflation exerts a positive and negative effect on budget deficit and money supply, respectively. The results from the impulse response function also indicate that inflation responds more positively to budget deficit shocks. However, it tends to respond negatively to money supply (M2) shocks. Also, budget deficit responds positively (negatively) to inflation (money supply [M2]) shocks. Furthermore, money supply responds positively (negatively) to budget deficit (inflation) shocks. Based on the weak exogeneity test, the result favours the fiscal theory of the price level in explaining the nexus between money supply, budget deficit and inflation in Ghana. A corollary of our results is that a reduction in government expenditure coupled with restrictive bureaucratic nature of government officials have the tendency of ensuring favourable and stable inflation in Ghana.
Keywords: 650; inflation; Budget deficit; Ghana; money supply; weak exogeneity test